2020
DOI: 10.1136/bmjgh-2019-002208
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in 46 low-income and middle-income countries: an appraisal of the most vulnerable groups of women using national health surveys

Abstract: IntroductionIntimate partner violence (IPV) against women is a critical public health issue that transcends social and economic boundaries and considered to be a major obstacle to the progress towards the 2030 women, children and adolescents’ health goals in low-income and middle-income countries (LMICs). Standardised IPV measures have been increasingly incorporated into Demographic and Health Surveys carried out in LMICs. Routine reporting and disaggregated analyses at country level are essential to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
153
3
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 29 publications
13
153
3
11
Order By: Relevance
“…More research is needed to clearly de ne the relationship between asset ownership and IPV, and the contextual or cultural factors that account for the difference in ndings across countries as it is important to understand how to advance women's asset ownership and economic status without increasing risk of IPV. For every increase in wealth quintile women had less than half the odds of experiencing lifetime IPV or IPV in the last 12 months, similar to ndings in prior studies in the 2014 KDHS(32) and in 46 LMICs(23).This study adds to the growing body of work on barriers to care in relation to IPV. Women who had no perceived barriers had half the odds of experiencing lifetime IPV or IPV in the last 12 months.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…More research is needed to clearly de ne the relationship between asset ownership and IPV, and the contextual or cultural factors that account for the difference in ndings across countries as it is important to understand how to advance women's asset ownership and economic status without increasing risk of IPV. For every increase in wealth quintile women had less than half the odds of experiencing lifetime IPV or IPV in the last 12 months, similar to ndings in prior studies in the 2014 KDHS(32) and in 46 LMICs(23).This study adds to the growing body of work on barriers to care in relation to IPV. Women who had no perceived barriers had half the odds of experiencing lifetime IPV or IPV in the last 12 months.…”
supporting
confidence: 84%
“…In Nicaragua and Tanzania, asset ownership was negatively associated with IPV and follow-up qualitative studies suggest that women in these countries felt increased autonomy and elevated respect from their husbands because of asset ownership (22). A multi-country study in 46 low-and-middle-income countries (LMICs) using wealth quintiles found that poorer women were more vulnerable to IPV (23). Studies on the relationship between poverty and IPV have similar ndings (16,24).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study conducted in low-income and middle-income countries including SSA found that female adolescents and younger adults of 15–19 years were at higher risk of IPV when compared with older groups of women. 4 This pattern was mostly observed in Namibia, Senegal, Zimbabwe, Cameroon, Sierra Leone, Congo, Zambia and Rwanda. However, different patterns regarding the higher risk of IPV in older rather than younger women were found particularly in countries outside SSA such as in Europe and Central Asia.…”
Section: Introductionmentioning
confidence: 96%
“…However, different patterns regarding the higher risk of IPV in older rather than younger women were found particularly in countries outside SSA such as in Europe and Central Asia. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation